SNACK FOOD SALES SYSTEM ON CV. USING JAYA AREN MICROSOFT VISUAL BASIC 6.0 APPLICATIONS - Dika Riswanudin; Rahayu Noveandini, S.Kom, MM Rahayu Noveandini, S.Kom, MM (Jurnal Sistem Informasi, 2010)
Writing is meant to design a computerized system in CV snack sales. Aren Jaya andhelp solve problems in CV sales transactions. Aren JAYA be more effective andefficient, especially in reducing kerangkapan data, giving the right information,quicklyand reliable.In this system the author uses the Microsoft Visual Basic 6.0. by using acomputerized system of cash sales of snack foods in CV. Aren JAYA, has advantagessuch as speed of obtaining information, data accuracy in the sense that there are nodata or data redudant that overlap and can reduce errors that occur in the sales processuntil the publication of the report.